PENGARUH PERILAKU ANCHORING DAN HERDING BIAS TERHADAP KEPUTUSAN INVESTASI SAHAM: Studi di Mahasiswa FBE Universitas Surabaya Semester 5 dan 7 Tahun 2022/2023 - Claudius Bona; Victor Marcelino Liangga (Jurusan Ilmu Ekonomi Prodi Ekonomi Pembangunan Fakultas Bisnis dan Ekonomika Universitas Surabaya, 2022)
Making an investment decision in the industrial revolution 4.0 is now a trend, especially in Indonesia. From KSEI's data in September 2022, there has been a 2.5-times increase in stock investment since the beginning of the pandemic in 2020. The significant increase in the number of stock investors, especially in students community during the pandemic has become an interesting factor to discuss. The influence of biased aspect of financial behavior in investing is often neglected by investors so they make an investment decision that are less than optimal. This study aims to determine the problems of investors' financial behavior aspects, especially anchoring behavior and herding bias related to stock investment decisions. Questionnaires are used as a tool to reveal respondents' opinions. Target respondents are students of the 5th and 7th semesters of the Faculty of Business and Economics, University of Surabaya. The data is then processed using SPSS 24 software. From the processing, research results’ show that anchoring bias has a positive and significant effect on investors' investment decisions. Moreover, for herding bias shows an insignificant effect for investment decisions. For future research, it is possible to examine the influence of other financial behaviors such as overconfidence and disposition effects on investment decisions among students.